EXTRACTION OF PECTIN FROM CITRUS SINENSIS FRUIT PEELS AND ITS EFFICIENCY AS A SUSPENDING AGENT - Ubieko, Edwin A; Onugwu, Adaeze L; Ogbonna, John DN; Okoye, Ebere; Nwakile, Callistus D; Attama, Anthony A (Universal Journal of Pharmaceutical Research, 2023)
Aim and objective: The study's objective was to evaluate the performance of Citrus sinensis pectin, which had been extracted and used as a suspending agent during the production of fixed-dose artemether-lumefantrine oral powder for suspension. Methods: The extracted pectin was used as an excipient to formulate an oral suspension powder of artemether and lumifantrine. Using analytical techniques including Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC), the compatibility of the formulation's constituents, active medicinal ingredients, and extracted pectin was evaluated. The formulated powder was tested for flow-ability, flow rate, sedimentation rate, re-dispersibility, dissolution rate, and short-term stability. Results: In several of the batches, the extracted pectin displayed suspending characteristics at concentrations as high as 3.0% w/v. Hausner's and Carr's indices for the created artemether-lumefantrine granules for oral suspension were 30°C, 0.35 g/mL, 0.42 g/mL, 1.20 g/mL, and 15%, respectively. The flow rate was 5.46 g/min, and the suspension's particle size was 7.20 g. The viscosities ranged from 19.50 to 27.20 cP and 12.80 to 21.30 cP at 30 rpm and 60 rpm, respectively. After 80 and 90 minutes, respectively, the dosage forms of artemether and lumefantrine released their respective 75 % w/w medications. Artemether; short-term stability was 91.7±0.01, 91.35±0.00, 90.13±0.02, 89.35±0.03 and 84.70±0.01 at days 0, 30, 60, 90, and 180, respectively. Lumefantrine; short-term stability was also 91.18±0.00, 91.17±0.03, 88.43±0.01, 82.75±0.00, and 81.77±0.02 Conclusion: According to this study, the artemether/lumefantrine oral suspension granules or powder made with the pectin extract had a great suspending effect. Peer Review History: Received: 3 June 2023; Revised: 8 July; Accepted: 26 August; Available online: 15 September 2023 Academic Editor: Dr. Muhammad Zahid Iqbal , AIMST University, Malaysia, drmmziqbal@gmail.com Reviewers: Ahmad Najib, Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Prof. Ali Gamal Ahmed Al-kaf, Sana'a university, Yemen, alialkaf21@gmail.com